The role of the public interest in competition law: a consideration of the public interest in merger control and exemptions in South Africa and how the public interest plays a more important role in the competition laws of South Africa and of developing nations - Teagu, Ian Graeme (Department of Commercial Law, 2026)
This paper considers the role accorded to, and importance of, the public interest objectives of the South African Competition Act1 (the Act). The aim of this paper is not to critique these objectives or to consider what role these objectives have played in South African competition jurisprudence in the eleven years since the enactment of the Act, but to accept such objectives and specifically consider what effect has been given to them in the other provisions of the Competition Act that expressly deal with the public interest, 2 and to argue that the competition authorities should not be too eager to diminish the importance of these sections, but that the public interest should play an important role in the competition law of South Africa and other developing nations, and as such, that the South African competition authorities should recognise this.